Vitamins in Cereals: A Critical Review of Content, Health Effects, Processing Losses, Bioaccessibility, Fortification, and Biofortification Strategies for Their Improvement - Garg, Monika; Sharma, Anjali; Vats, Shreya; Tiwari, Vandita; Kumari, Anita; Mishra, Vibhu; Krishania, Meena (Frontiers in Nutrition, 2021)
Around the world, cereals are stapled foods and good sources of vitamins A, B, and E. As cereals are inexpensive and consumed in large quantities, attempts are being made to enrich cereals using fortification and biofortification in order to address vitamin deficiency disorders in a vulnerable population. The processing and cooking of cereals significantly affect vitamin content. Depending on grain structure, milling can substantially reduce vitamin content, while cooking methods can significantly impact vitamin retention and bioaccessibility. Pressure cooking has been reported to result in large vitamin losses, whereas minimal vitamin loss was observed following boiling. The fortification of cereal flour with vitamins B1, B2, B3, and B9, which are commonly deficient, has been recommended; and in addition, region-specific fortification using either synthetic or biological vitamins has been suggested. Biofortification is a relatively new concept and has been explored as a method to generate vitamin-rich crops. Once developed, biofortified crops can be utilized for several years. A recent cereal biofortification success story is the enrichment of maize with provitamin A carotenoids.